Physical characterization of sub‐32‐nm semiconductor materials and processes using advanced ion beam–based analytical techniques. (27th March 2012) - Hopstaken, M. J. P.; Pfeiffer, D.; Copel, M.; Gordon, M. S.; Ando, T.; Narayanan, V.; Jagannathan, H.; Molis, S.; Wahl, J. A.; Bu, H.; Sadana, D. K.; Czornomaz, L.; et al.
<x xml:space="preserve">Abstract</x> The authors have addressed the application of advanced ion beam–based analytical techniques to various physical characterization aspects in sub‐32‐nm semiconductor front‐end‐of‐line materials and processes. We have presented the application of 18O‐isotope labeling in combination with SIMS depth profiling to follow O‐migration in high‐k/metal gate stacks. We have also demonstrated the application of complementary low‐energy ion scattering and time‐of‐flight SIMS surface analysis to determine high‐k thin film closure and growth mode for different deposition techniques. We have also proposed alternative Dynamic Secondary Ion Mass Spectrometry (DSIMS) protocols for the quantitative analysis of phosphorous ultra‐shallow junctions, resulting in more accurate near‐surface P‐profile and in situ B‐doped Si1−xGex epitaxial films with explicit correction of sputter and ionization yield variations as function of [Ge]. We have demonstrated the feasibility of backside SIMS on appropriate III–V high‐mobility channel stacks, resulting in unprecedented depth resolution at the source/drain metal–contact/III–V interface. Copyright © 2012 John Wiley & Sons, Ltd.